Polyethylene polymer modified bitumen: Process optimization and modeling of linear viscoelastic rheological properties using response surface methodology - Bala, N. (Medwell Journals, 2018)
Polymers are generally, applied to improve the durability and performance of asphalt pavement structures against premature defects. In this study, the optimization of polyethylene polymer for bitumen modification has been investigated to determine optimum proportions for higher linear viscoelastic properties. A Response Surface Methodology (RSM) Central Composite Design (CCD) design was applied with two with two independent variables polyethylene content and temperature and three linear viscoelastic responses Complex Modulus (CM), Phase Angle (PA) and Viscosity (V). The results showed that a high correlation coefficient (R2) of 0.9998, 0.9962 and 0.9998 were obtained for complex modulus, phase angle and viscosity which indicates that, the model's values are in strong correlation with the values of the experiment. The model also indicates that temperature is the most influencing factor among the two independent variables responsible for linear viscoelastic properties of the modified binder. Based on numerical optimization using proposed quadratic model, the optimum mix can be achieved with a 4 polyethylene at a temperature of 25Â°C. Â© 2018, Medwell Journals.